Digital Maturity of Core Enterprises: Assessment and Impact on Territorial Development - Овчинникова, Оксана Петровна; Kharlamov , Maksim M. (Economy of Regions, 2022)
Digital maturity of an enterprise and, subsequently, the impact of digital maturity of a core enterprise on the economic and social development of a territory remain an underdeveloped topic. Based on a hypothesis that digital maturity is a trigger for territorial development, this study assesses the digital maturity of core enterprises, i.e. their readiness to implement new technologies in all business processes for improving productivity and competitiveness. Digital maturity levels were determined according to the identification of strategic areas of activity, including unique technological competencies and personnel work. The proposed strategy for developing a new digital maturity model of enterprises takes into account the structure and content of existing models, since there are currently no best practices that can be scaled. In order to analyse digital maturity levels in detail, a survey of the expert community, as well interviews with digital transformation specialists were conducted. As a result, we constructed a digital maturity model of core enterprises that includes five levels, characterising organisational, production, human resources and external (impact on territorial development) processes. The parameter of the job creation multiplier was tested in the developed model. As a result, the conducted research confirmed the hypothesis that digital development of enterprises directly affects the territorial development. This, on the one hand, opens new opportunities for the socio-economic development of territories, and, on the other hand, places new demands on the digital infrastructure, quality of provided services, personnel competence, etc. The research results are of interest to state and local authorities, industry core enterprises, and the scientific community, as the obtained findings determine the prospects for studying digital maturity in relation to territorial and industrial development.